The year in tech 2023. (Insights you need from Harvard Business Review., 2023)
"From emotional AI and hybrid collaboration tools to crypto for business and no-code apps, tech innovations are reshaping organizations from the factory floor to the C-suite. What should you and your company be doing now to take advantage of the opportunities these technologies are creating-and to avoid falling victim to disruption? The Year in Tech, 2023: The Insights You Need from Harvard Business Review will help you understand what the latest and most important applications of new tech mean for your organization and how you can use them to compete and win in today's turbulent business environment. Business is changing. Will you adapt or be left behind?"--